Biomass and carbon stocks in restored Atlantic Forests: a systematic review - Mores, Guilherme José [UNESP]; Ballarin, Caio Simões [UNESP]; Podadera, Diego Sotto [UNESP]; Engel, Vera Lex [UNESP] (John Wiley & Sons, Inc., 2025)
In restored tropical forests, a better understanding of biomass and carbon estimation methods is needed—especially biomass assessment, allometric equation choice, and the influence of local conditions. Understanding these factors is critical given forests’ role in sequestering and storing atmospheric carbon. We conducted a systematic review on the state of the art in estimating plant biomass and carbon storage in restored forests within the Atlantic Forest. We examined the biomass measurement methods, the factors influencing biomass productivity, and estimated the time required for restored forests to attain biomass levels observed in conserved forests. For each study, we investigated: (1) how biomass stocks were assessed; (2) the allometric equations used for estimation; (3) and the restoration techniques applied alongside the biotic and abiotic conditions at each site. We also examined whether local climatic conditions, forest age, and the number of planted species influenced biomass accumulation. Despite the limited number of studies assessing carbon stocks in restored Atlantic Forests, publications have increased recently. However, the equations used to estimate carbon stocks were mainly adjusted to young forests (5–17 years). Moreover, studies lack a standardized protocol for converting biomass into carbon, and few assessing root biomass. We found that age is the key factor explaining biomass accumulation. Finally, our projections indicate forests over 25 years of restoration likely exhibit plant biomass similar to conserved forests. Still, different protocols and equations for estimating plant biomass accumulation may lead to under- or overestimates compared to the projections presented here.
Biomassa e estoques de carbono em florestas atlânticas restauradas: uma revisão sistemática
Keywords: Allometric equations; Bibliometric analysis; Carbon stock; Ecosystem services; Forest restoration